2019
DOI: 10.1093/sysbio/syz048
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Approach Using Phylogenomics and High-Resolution X-Ray Computed Tomography for Species Delimitation in Cryptic Taxa

Abstract: Morphologically cryptic taxa have proved to be a long-standing challenge for taxonomists. Lineages that show strong genomic structuring across the landscape but are phenotypically similar pose a conundrum, with traditional morphological analyses of these cryptic lineages struggling to keep up with species delimitation advances. Micro X-ray computed tomography (CT) combined with geometric morphometric analyses provides a promising avenue for identification of morphologically cryptic taxa, given its ability to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…Previous analyses of morphological characters have shown that scale counts are not discreet but instead continuous between the currently named taxa (Burbrink, ), whether this is the case for the eastern and western populations of P. guttatus is not yet known. Morphological variation among these recently evolved taxa might be subtle (e.g., differences in head shape variation; Ruane, ) and may be detected using high‐resolution morphological data from specimen‐based studies (Chaplin, Sumner, Hipsley, & Melville, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses of morphological characters have shown that scale counts are not discreet but instead continuous between the currently named taxa (Burbrink, ), whether this is the case for the eastern and western populations of P. guttatus is not yet known. Morphological variation among these recently evolved taxa might be subtle (e.g., differences in head shape variation; Ruane, ) and may be detected using high‐resolution morphological data from specimen‐based studies (Chaplin, Sumner, Hipsley, & Melville, ).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological variation among these recently evolved taxa might be subtle (e.g., differences in head shape variation; Ruane, 2015) and may be detected using high-resolution morphological data from specimen-based studies (Chaplin, Sumner, Hipsley, & Melville, 2019).…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…Intrinsic hindrances, which we define as properties of the species themselves that complicate taxonomy, such as morphologically cryptic species, can be overcome by diversification of data types in species delimitation; in most cases, diagnostic features of cryptic species can be found with the right methods and datasets (e.g. micro-CT 2,3 ). Extrinsic hindrances, which typically concern nomenclatural issues but can also relate, for example, to the lack of availability of specimen material, are less often discussed, but can be equally difficult, or even more difficult, to overcome.…”
mentioning
confidence: 99%
“…Common biodiversity metrics such as species identity, richness, and evenness are inferable from μCT data, e.g. 27 , 28 , especially for cryptic taxa and species complexes with few observable differences 29 31 . Therefore, optimization of the scanning process for high resolution 3D images of multiple specimens would not only contribute to our understanding of how biodiversity responds to global change, but also to the value of museum collections and researchers’ abilities to access them digitally.…”
Section: Introductionmentioning
confidence: 99%